The practice of SAP software in the accounts department : the case study of Permodalan Nasional Berhad (PNB) / Farah Shahida Sumaiyyah Ramle - Sumaiyyah Ramle, Farah Shahida (Faculty of Business and Management, 2009)
This paper investigates the practicality of SAP Software in the Accounts Department of Permodalan Nasional Berhad (PNB). It consists of investigation of the differences between software-based accounting system and paper-based accounting system. A mixed method research approach was used with strategies of inquiry that involve quantitative and qualitative data collection. In order to get an in depth views of the research, questionnaire were distributed to all the employees in PNB Accounts Department. Based on the questionnaire findings, interviews were conducted among the Executives and Senior Executives of PNB Accounts Department in order to confirm the findings of the questionnaire. The interviews involve the Executives and Senior Executives because they are the one who use the software regularly. The findings presented will focus on three main issues. Firstly, the practicality of the SAP Software in the Accounts Department; to identify the existing differences between softwarebased accounting system and paper-based accounting system; and finally, what can the researcher suggest in order enhancing the efficiency of using the SAP Software.